Familial Spontaneous Pneumothorax in Three Siblings Including Identical Twins - Kuwahara, Osamu; Fujiwara, Kiyohiro; Dohi, Hideki; Furuyama, Jun-ichi; Yamamoto, Yoshihiro; Moriguchi, Akira; Ikeda, Masahito (Nihon Kyōbu Shikkan Gakkai zasshi, 1989)
Two identical twin brothers and their sister who suffered from spontaneous pneumothorax (ages at onset, 18, 22 and 20 years) were admitted to our hospital. Their symptoms and clinical courses were similar and all three were finally treated by thoracotomy. No other members of their family had any history of spontaneous pneumothorax. None of these cases presented any abnormal level of serum ACE or α1-antitripsin. In order to establish the monozygosity of the brothers more accurately, we examined restriction fragment length polymorphisms (RFLPs) which were shown as the band patterns of hypervariable minisatellite regions in human genomes. However there have been few reports of spontaneous pneumothorax in identical twins, but the onset of the disease tends to be the same as in our cases, suggesting a genetical background of spontaneous pneumothorax.